Reconstruction of the MIS 5.5, 5.3 and 5.1 coastal terraces in Latium (central Italy): A re-evaluation of the sea-level history in the Mediterranean Sea during the last interglacial. (10th August 2019) - Marra, Fabrizio; Bahain, Jean-Jacques; Jicha, Brian R.; Nomade, Sebastien; Palladino, Danilo M.; Pereira, Alison; Tolomei, Cristiano; Voinchet, Pierre; Anzidei, Marco; Aureli, Daniele; Ceruleo, Piero; Falguères, Cristophe; et al.
Abstract: We present a geomorphological, stratigraphical and geochronological study reconstructing a suite of paleo-surfaces in a 200 km-long coastal sector of the central Tyrrhenian Sea between Argentario and Circeo promontories. Identification of the near-shore deposits associated with these paleo-surfaces allow us to define corresponding marine terraces and paleo sea-levels. 40 Ar/ 39 Ar and ESR/U-Th geochronologic constraints on key deposits provide correlation with the terraces previously recognized in the coast of central Latium, refining their correlation with the Marine Isotopic Stages. Results of this study enable us to: Propose a re-assessment of the ages for the sea-level markers of MIS 5.5, 5.3, 5.1 in the central Tyrrhenian Sea; Suggest that a continuous tectonic uplift with an average rate of 0.224 mm/yr affects the Latium coast since 200 ka; Provide new evidence for a MIS 5.5 paleo-sea level marker occurring at ~35 m a.s.l. on the coastal sector extending from Montalto di Castro to Latina, while it possibly drops down and connects to a paleo sea-level ranging 10 - 5 m between Monte Circeo and Gaeta, previously attributed to this interglacial; Discussing possible evidence of similar elevation of the sea level during MIS 5.5, 5.3 and 5.1 interglacials in the Tyrrhenian Sea; Compare this datum with those from the western Pacific and several coral reefs, where the differences with respect to tectonically stable regions were attributed either to tectonics or to the Glacial Isostatic Adjustment, showing that the presented record of sea-level markers may have a strong impact on modeling the post-glacial effects in the Mediterranean Sea and on the paleoclimatic and paleoceanographic studies in this region.